Quantitative determination of nine water‐soluble vitamins in the complex matrix of corn steep liquor for raw material quality assessment. Issue 8 (22nd February 2017) - Hofer, Alexandra; Herwig, Christoph
Abstract: BACKGROUND: Although raw materials such as corn steep liquor (CSL) are commonly used as supplements in media for biotechnological production of valuable products such as antibiotics, however, determination of the composition of CSL is still a scarcely explored field of research. Especially for some B‐vitamins, which are badly soluble and compose just a small fraction in CSL, no adequate analytical method has been published yet. RESULTS: In this study we adopted a RP‐HPLC‐UV method for the simultaneous determination of nine water‐soluble vitamins (biotin, cyanocobalamin, folic acid, niacin amide, nicotinic acid, pantothenic acid, pyridoxine, riboflavin, thiamine) and evaluated six different methods for the extraction of vitamins from CSL (two liquid–liquid extractions and four enzymatic extractions). The proposed method showed relative errors of about 2%; LOD and LOQ were ranged between 0.07 and 0.875 µg mL −1 and 0.2 and 2.5 µg mL −1, respectively, deviating just for the low absorbing pantothenic acid. The method was successfully applied to eight CSL samples which differed in manufacturer and corn quality (dried or wet corn). Seven out of nine vitamins could be identified in CSL and correlations between some vitamins and manufacturer (i.e. nicotinic acid, pantothenic acid and biotin) and quality (i.e. thiamine, pyridoxine and cyanocobalamin), respectively, could be observed. CONCLUSION: The variation in vitamin composition found in the different CSL samples points out the importance of an incoming inspection of CSL to reduce variations in bioprocesses which are caused by raw material variability. This contribution provides a valuable quantitative tool for this task. © 2017 Society of Chemical Industry